Social Criticism Of Bob Dylan's Song Lyrics: A Sociological Study Of Literature - Muhadi, Hafid, Dr. M.Thoyibi, M.S, Nur Hidayat, M.Pd (2014)
This research paper aimed to show visible image of Bob Dylan's song lyrics which analyzed by using sociology of literature. The objective of the research are to analyzing the sonnet based on the structural element and to analyzed the lyrics based on sociology of literature by indentifying from relationship between social historical background of United States in The Middle of Twentieth Century. This research paper belongs to qualitative research. Data of the research is the text from and it has taken based on the theme, thereabout consisting 15 song's a thematically. The primary data of the research is the Bob Dylan's song lyrics from the website with address www.azlyrics.com and secondary data of the research are biography of the author that written by Jeremy Robert entitled "Bob Voice of a Generation", websites, and other source about the lyrics, the social background of American society that support the analysis. The method to analyze of this data is descriptive analysis. The researcher comes to the conclusion as follows. Firstly, based on the structural analysis, it shows that social criticism of Bob Dylan theme on his lyrics. Correlating by theme, Dylan describes the social criticism actually. Secondly, based on the sociology analysis the author wants to show a social criticism toward social condition of American society which showed from the characterization on the lyrics.